“The Influence Of Internal Audit Toward Fraud Prevention In One Of Banks In Bandung” - et. al., Ignatius Oki Dewa Brata, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine how the influence of internal audit against fraud in one of Banks in Bandung. Supporting factors in this study are Internal Audit as an independent variable and Prevention of Fraud as the dependent variable. The research method used in this research is a descriptive research method with case study studies. Data collection techniques used in this study is to use a questionnaire. The sampling technique used in this study uses non-probability sampling techniques. This study uses a simple linear regression analysis method. The results showed that the Internal Audit and the Prevention of Fraud (Fraud) showed in good condition. And it can be concluded that the internal audit has a significant effect on the increase in fraud.